Growth response, nutrient digestibility and physical body measurements of Grasscutter (Thryonomys swinderianus) fed whole cassava (Manihot esculenta) root meal fortified with selected fermented protein sources (Journal of the Bangladesh Agricultural University, 2018)
Grasscutter serves as a major tool for improved household income generation, nutrition and bio-diversity in Nigeria. It provides a quick turnover, foreign exchange earner and reduce unemployment rate of the country.In order to assess the feeding values of concentrates used as supplement, studies were conducted in captivity to evaluate the performance of Grasscutter (Thryonomys swinderianus) using 20 growing Grasscutters comprising 16 females and 4 males who were balanced for weight and grouped into four treatments. Inclusion of whole cassava meal that was incorporated at 80% of the total bulk acted as the control(T0) while 10% of whole cassava root meal was replaced by fermented soybean meal in (T1), fermented locust bean meal in (T2) and fermented melon seed meal in (T3) respectively were considered as experimental using a complete randomized design. Elephant grass (Pennisetum purpureum) was used as the basal diet and water were given ad libitum. There were significant difference in the final body weight gains (P